Carrier-Transport Study of Gallium Arsenide Hillock Defects. (October 2019) - Xiao, Chuanxiao; Jiang, Chun-Sheng; Liu, Jun; Norman, Andrew; Moseley, John; Schulte, Kevin; Ptak, Aaron J.; Gorman, Brian; Al-Jassim, Mowafak; Haegel, Nancy M.; Moutinho, Helio
Abstract: Single-crystalline gallium arsenide (GaAs) grown by various techniques can exhibit hillock defects on the surface when sub-optimal growth conditions are employed. The defects act as nonradiative recombination centers and limit solar cell performance. In this paper, we applied near-field transport imaging to study hillock defects in a GaAs thin film. On the same defects, we also performed near-field cathodoluminescence, standard cathodoluminescence, electron-backscattered diffraction, transmission electron microscopy, and energy-dispersive X-ray spectrometry. We found that the luminescence intensity around the hillock area is two orders of magnitude lower than on the area without hillock defects in the millimeter region, and the excess carrier diffusion length is degraded by at least a factor of five with significant local variation. The optical and transport properties are affected over a significantly larger region than the observed topography and crystallographic and chemical compositions associated with the defect.